Clinical evaluation of corneal ulcer with a portable and smartphone-attachable slit lamp device: Smart Eye Camera - Sadegh Ghafarian; Ahmad Masoumi; Seyed Ali Tabatabaei; Mehdi Yaseri; Eisuke Shimizu; Shintaro Nakayama; Rohan Jeetendra Khemlani; Hiroki Nishimura; Hassan Asadigandomani (Scientific Reports)
Abstract Corneal ulcer is one of the most important ophthalmic emergencies. A portable, recordable, and smartphone-attachable slit-lamp device called the “Smart Eye Camera” (SEC) is introduced to compare evaluating corneal ulcers between the SEC and the conventional slit-lamp. A total of 110 participants were included in the study, consisting of 55 patients with corneal ulcers and 55 age- and gender-matched healthy volunteers as controls. The participants were first subjected to examination by a conventional slit lamp. The video recording with SEC and imaging with a slit lamp were done by a non-medical person. Both SEC videos and slit-lamp photos were reported by two independent ophthalmologists and compared with a slit-lamp examination as a gold standard. The average age of the study participants was 48.85 ± 20.45 years and 68 participants (61.8%) were male. All corneal ulcers were detected by two ophthalmologists using SEC. Ulcer size evaluated in slit lamp and SEC horizontally (Intraclass Correlation Coefficient (ICC); 0.90, 95% CI; 0.84–0.94) and vertically (ICC; 0.90, 95% CI; 0.84–0.94) is correlated about 90%. Hypopyon size (ICC; 0.95, 95% CI; 0.92–0.97), and corneal epithelial defect (CED) size horizontally (ICC; 0.94, 95% CI; 0.91–0.96) and vertically (ICC; 0.94, 95% CI; 0.91–0.96) also correlated about 94%. The infiltration pattern evaluated by SEC was consistent with the pattern evaluated in slit lamps in more than 80% of patients. The SEC is so accurate in diagnosing corneal ulcers and its reliability makes it a valuable telemedicine device.